Association between improved metabolic risk factors and perceived fatigue during dietary intervention trial in relapsing-remitting multiple sclerosis: A secondary analysis of the WAVES trial - Villa, Aneli T.; Tu, Betty H.; Titcomb, Tyler J.; Saxby, Solange M.; Shemirani, Farnoosh; Ten Eyck, Patrick; Rubenstein, Linda M.; Snetselaar, Linda G.; Wahls, Terry L. (Frontiers in Neurology, 2023)
Background Preliminary dietary intervention trials with the low-saturated fat (Swank) and modified Paleolithic elimination (Wahls) diets have shown favorable effects on fatigue among people with multiple sclerosis (MS); however, their impact on metabolic health is unknown. Objective To evaluate the impact of the Swank and Wahls diets on markers of metabolic health and to determine the association and mediation effect between changes in metabolic health and perceived fatigue among people with relapsing-remitting MS (RRMS). Methods As part of a randomized parallel-arm trial, vital signs, blood metabolic biomarkers, and the fatigue scale for motor and cognitive functions (FSMC) were collected from participants with relapsing-remitting MS (n = 77) at four study visits spaced 12 weeks apart: (1) run-in, (2) baseline, (3) 12-weeks, and (4) 24-weeks. Participants followed their usual diet at run-in, then were randomized at baseline to either the Swank or Wahls diets and followed for 24 weeks. Results Both groups had significant reductions in weight, body mass index (BMI), total cholesterol, and low-density lipoprotein (LDL) at 12- and 24-weeks compared to respective baseline values (p ≤ 0.04 for all). The Swank group also had a significant reduction in high-density lipoprotein (HDL) at 12- and 24-weeks (p = 0.0001 and p = 0.02, respectively), while the Wahls group had significant reductions in diastolic blood pressure (DBP). In addition, both groups had significant reductions in FSMC total perceived fatigue and the motor and cognitive fatigue subscales at 12- and 24-weeks (p ≤ 0.01 for all); however, change in the cognitive subscale was not significant at 12-weeks in the Swank group (p = 0.06). Furthermore, the favorable effects, of both diets, on markers of metabolic health were not associated with and did not mediate the effect of the diets on perceived fatigue (p > 0.05 for all). Conclusion Both diets lead to significant reductions in perceived fatigue, weight, BMI, total cholesterol, and LDL, but the significant reductions in perceived fatigue were independent of changes in markers of metabolic health.